Plaque, caries level and oral hygiene habits in young patients receiving orthodontic treatment (2010)
To assess plaque, caries, and oral hygiene habits amongst patients receiving fixed-orthodontic treatment at the Dental-Clinic, Universidad-El-Bosque, Bogotá, Colombia. Test-group: 74 12-29-year-olds receiving fixed-orthodontic treatment; reference-group: 63 12-29-year-olds before they started the orthodontic treatment. Visual examinations (one examiner) recorded the following: Ortho-plaque-Index (OPI) expressed per patient as good, fair and poor-oral-hygiene. Caries was scored with the modified-ICDAS-II criteria as: 0-sound; 1B/1W-brown/white-opacity-after-air-drying; 2B/2W-brown/white-opacity-without-air-drying; 3-microcavity; 4-underlying-shadow; 5/6-distinct/extensive-cavity. Filled/missing surfaces due-to-caries and caries-lesions on buccal surfaces at three sites around the brackets were recorded. A 7-item self-administered oral-hygiene habits' questionnaire was used. Chi-square test revealed that the oral-hygiene level was significantly better in the reference group compared to the test group (p < 0.05). The traditional mean DMF-S was 6.7 +/- 6.3 in the test- and 6.2 +/- 5.9 in the reference-group (p > 0.05). When adding modified-ICDAS-II lesions scores 1-4, the figure increased to 23.6 +/- 9.4 in the test- and to 13.6 +/- 10.3 in the reference-group (p < 0.001). A total of 96% had > or = 1 white-opacity in the test group versus 56% in the reference group (P < 0.001). In the test-group the buccal-surfaces accounted for most white-opacities and close to 1/3 of these lesions on the upper-anterior teeth were located around the brackets. The questionnaire disclosed that 58% in the test- vs. 44% in the reference-group did not accept having dental caries lesions during the orthodontic treatment. The results showed a high prevalence of white-opacities related to orthodontic appliances and indicate the need to implement preventive programmes at the dental clinic.